ENHANCING STUDENTS’ VOCABULARY MASTERY BY USING FRONTLOADING STRATEGY IN THE GOOGLE CLASSROOM APPLICATION AT THE TENTH GRADE NATURAL SCIENCE 1 OF SMA NEGERI 4 METRO - Kristiani, Francisca Selly; Siagiyanto, Bambang Eko; Kusumawati, Fitri Palupi (Journal of English Education and Enterpreneurship (JEEP), 2021)
The goal is to identify the problems of students in tenth grade natural science 1 to improve the quality of learning, especially for vocabulary. The teacher provides students with a worksheet contain words such as synnonim, antonym and part of speech of the words. This research is Classroom Action Research. Those were reconnaissance, planning, action, observation, and reflection. The subjects were 33 students at tenth grade natural science 1 of SMA Negeri 4 Metro. The criteria of succes determines by researcher successful if 75% of 33 students follow the learning process well and also give good responses to the teacher and if the 75% from 33 students get score 70. The research was done in two cycles and obtained the qualitative and quantitative data. The data collection instruments were observation checklists, interview guidelines, and tests. The data were in the observation checklists, interview transcripts, and scores.The result of the research showed that the use of frontloading strategy in the teaching and learning process significantly improved the students’ vocabulary mastery. the students could improve their vocabulary mastery by looking for vocabulary related to the picture given and also the picture was described then the students entered it as the KWL format which is one of the frontloading srategies. Based on the quantitative data, the students’ mean value for the vocabulary skills improved. In the pre – test, the students’ mean value was 61.96 Then, after Cycle 1 (post – test 1), the students’ mean value of post – test 1 was 68.33 . At last, after Cycle 2 (post – test 2), the students’ mean value in the post – test 2 was 86.21 . In conclusion, the use of frontloading strategy can improve the students’ vocabulary mastery significantly.